Leading Determinants for Disease-Free Status in Community-Dwelling Middle-Aged Men and Women: A 9-Year Follow-Up Cohort Study - Shang, Xianwen; Wang, Wei; Keel, Stuart; Wu, Jinrong; He, Mingguang; Zhang, Lei (Frontiers in Public Health, 2019)
Background Identifying leading determinants for healthy ageing may provide evidence for action priorities, which is imperative for public health with an expanding aged population worldwide. This study aimed to identify leading determinants, especially modifiable factors for healthy ageing using machine learning methods. Methods We included 52,036 participants aged 45-64 years from the 45 and Up Study who were free of 13 predefined chronic conditions at baseline (2006-2009). Healthy ageing was defined as participants ageing from 45-64 years at baseline to 55-75 years at the end of the follow-up (December 31, 2016) without developing any of the thirteen chronic conditions. We used machine learning methods to evaluate the importance of 40 potential predictors and analyzed the association between the number of leading modifiable healthy factors and healthy ageing. Results Healthy ageing was found in about half of both men and women during a mean nine-year follow-up. The five most common leading predictors were body mass index (6.4-9.5% of total variance), self-rated health (5.2-8.2%), self-rated quality of life (4.1-6.8%), red meat intake (4.5-6.5%), and chicken intake (4.5-5.9%) in both genders. Modifiable behavioral factors including body mass index, diets, smoking, alcohol consumption and physical activity, contributed to 37.2-40.3% of total variance. Participants having six or more modifiable health factors were 1.63-8.76 times more likely to remain healthy ageing and had 0.60-2.49 more healthy ageing years (out of nine-year follow-up) than those having two or fewer. Non-behavioral factors including low levels of education and income and high relative socioeconomic disadvantage, were leading risk factors for healthy ageing. Conclusions Body mass index, diets, smoking, alcohol consumption and physical activity are key factors for healthy ageing promotion. Individuals with low socioeconomic status are more in need of care.